DAMPAK KEMAJUAN TEKNOLOGI INFORMASI TERHADAP BIDANG AKUNTANSI MANAJEMEN - meldona_nurlatifa@yahoo.co.uk, Meldona (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2010)
Information technology development has significantly changed the businesses. Various kinds of information systems which use information technology are Electronic Data Processing Systems (EDP), Data Processing Systems (DPS), Decision Support System (DSS), Management Information System (MIS), Executive Information Systems (EIS), Expert System (ES) and Accounting Information System (AIS). The development of information technology has also influenced management accounting dicipline as the producer of information for planning, controling and decision making. These influences, of course, has advantages and diadvantages for the companies. Keywords: information technology, management accounting,decision making.